Predictors of haemodynamic performance in patients with aortic stenosis and small annulus undergoing TAVI with self-expandable valves. (25th November 2020) - Chiarito, M; Regazzoli, D; Cannata, F; Pagnesi, M; Pagnotta, P.A; Stefanini, G.G; Barbanti, M; De Marco, F; Adamo, M; Van Mieghem, N.M; Kim, W.K; Maisano, F; et al.
Abstract: Background: Small aortic annular size is one of the most important predictor of poor hemodynamic and clinical outcomes in patients treated for aortic stenosis. Post-hoc analyses of pivotal trials showed that transcatheter aortic valve intervention (TAVI) offer better outcomes then surgery in patients with small aortic annulus, especially with self-expandable valves (SEV). However, data about SEVs comparison in this population are limited. Purpose: Our aim is to assess how valve design and oversizing, with anatomical and echographic features, impact on the hemodynamic performance of SEVs in TAVI patients with small aortic annulus. Methods: The TAVI SMALL registry enrolled 859 patients with small aortic annulus (CT-scan annular perimeter≤72 mm or area ≤400 mm 2 ) treated for aortic stenosis with currently available SEVs (Evolut R=397; Evolut PRO =84; Acurate Neo=140; Acurate TA= 61; Portico=177) at 9 European centers between 2011 and 2018. We performed multivariable backward logistic regression analyses to identify predictors of high postprocedural mean gradient, moderate-to-severe PPM, and moderate-to-severe para-valvular leak (PVL). Results: After adjustment for LVEF, we identified annular perimeter and percentage of oversizing as independent predictors of lower post-procedural mean gradient. Implantation of intra-annular rather than supra-annular bioprosthesis was the only independent predictor of moderate-to-severe PPM. Predictors of moderate-to-severe PVL are reported in the Table. Conclusions: Among patients with aortic stenosis and small aortic annulus treated with transcatheter SEVs, use of supra-annular bioproshtesis and oversizing were associated with improved valve performance. Funding Acknowledgement: Type of funding source: None